Food safety management programs : applications, best practices, and compliance - Newslow, Debby L. (CRC Press, 2014)
"For more than 20 years, we have heard talk about International Standardization Organization (ISO)-based standards and whether or not there is a place for these standards in the food industry. The majority of the food industry felt we had all the regulations and requirements necessary to produce safe products of the highest quality. Is this really true? ISO compliance was only required if the product was shipped overseas. ISO required too much documentation. It cost too much. It just wasn't needed. It was difficult to understand the internal advantages of having a structured system. Over the years, some companies who decided to try the ISO-based standards system have seen many advantages; others still wonder if it was worthwhile. It is hard to put a dollar savings on something like a recall that didn't happen! So now, in today's world, we ask again, "Is there a place in the food industry for structured management systems?" There is no doubt that a structured, effective management system can enhance an organization. It is also evident that an inadequate, poorly designed system can be a true detriment to an organization. This statement is based on many years of experience and first-hand exposure to many different food sectors, ranging from growing and producing the raw products and materials to manufacturing sites, restaurants, and grocery stores that have direct contact with the consumer. The value of an effective, well-defined, implemented, and maintained food management system is priceless. This type of system focuses on food safety, continuous improvement, and meeting customer requirements"-- Provided by publisher.
Keywords: Food industry and trade -- Quality control.; Food industry and trade -- Management.; Food -- Safety measures.; elektronické knihy; electronic books